Uncovering The Power of Dhikr from The Perspective of Sufism and Its Relevance in Resisting the Destruction of The World - Karo-Karo, Denni; Ahmad Zuhri; Simamora, Nur Aisah (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2024)
This article examines the power of dhikr in the perspective of Sufism and its relevance in resisting the destruction of the world. Zikr, which etymologically comes from the word dzakara which means to remember, is a spiritual practice that aims to get closer to God by filling the mind and heart with holy words. This article uses a qualitative research method with a literature review approach. In the context of Sufism, dhikr is not only seen as a ritual activity, but also as a means to improve the spiritual and moral intelligence of individuals. Sufism itself is a self-practice that aims to form a person who is submissive and obedient to God's commands, as well as overcoming the ego that can keep humans away from divine values. This study found that dhikr has an important role in overcoming the challenges of modernity that can threaten human spiritual balance. In an increasingly materialistic and fragmented world, dhikr helps individuals to nurture God-consciousness and maintain inner balance. In addition, dhikr also serves as a tool to overcome the negative influences of globalization and modernization that can cause moral and spiritual destruction. Thus, dhikr in the Sufism perspective can be a strong hold to withstand the destruction of the world by building a solid spiritual foundation within individuals and society. Through literature analysis, this article asserts that dhikr is not only a spiritual practice but also has a significant social impact.